Pengaruh Karakteristik Pekerjaan Dan Komitmen Organisasi Terhadap Organizational Citizenzhip Behavior Pada Kantor Dinas Perhubungan Provinsi Aceh - Syamsuddin, Nurfiani; Susanti, Susanti; Ramadhan, Taufiq (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2022)
Human Resources (HR) is the main driving factor in an organization because the existence of an organization also depends on the humans involved behind it. Organizational Citizenship Behavior (OCB) is an employee voluntary behavior that is not directly related to rewards, but contributes to organizational effectiveness. Problems about low organizational citizenship behavior can occur in an organization. This study aims to determine the effect of job characteristics and organizational commitment on organizational citizenship behavior at the Aceh Provincial Transportation Office. The population of this study were all employees at the Aceh Provincial Transportation Service Office as many as 264 people and the sampling technique used the slovin technique in order to obtain 72 employees. The model used in this study is multiple linear regression analysis. The results of the study indicate that job characteristics and organizational commitment simultaneously and partially have a significant effect on organizational citizenship behavior at the Aceh Provincial Transportation Office. The value of the correlation coefficient (R) of 0.723 means that organizational citizenship behavior at the Aceh Provincial Transportation Service Office has a close and positive relationship with job characteristics and organizational commitment of 72.3%. While the coefficient of determination (R2) is 0.523, meaning that any changes in the dependent variable, namely organizational citizenship behavior at the Aceh Provincial Transportation Service Office, can be explained by changes in the job characteristics variable (X1) and organizational commitment (X2) of 0.523 or 52.3% and the remaining 47.7% is explained by other variables outside of this research, for example compensation, promotion, work environment, work motivation, organizational culture, work discipline and others.